EVEKTIVITAS PENGGUNAAN TIRFOR DAN KATROL TUAS PADA PENEBANGAN JATI DI JAWA TENGAH - Maman Mansyur Idris; Zakaria Basari; Soenarno Soenarno (Pusat Penelitian dan Pengembangan Hasil Hutan, 1985)
The study of tirfor and lever block effectiveness in teak felling was conducted at the Perum Perhutani (The Forest State Corporation) Unit I Central Java on June 1982 and July 1983. Both felling equipments were used cut the press down to the desired directions.The purpose of the study is to find out the effects of tirfor and lever block on log damager in felling actives. The study was carried out in a three locations with different slopes i.e. 0 -10% and 11 – 30%.The result indicates that on the 11 - 30% slope, the tirfor reduces 5.25% log damages compared with that of the lever block. It is concluded that in sloped areas tirfor is more efective then lever block.